(3TckQGs - (3EcRGcJs; (3eMeO , aGWeI GdRgQGA ahRjs ((3GdLjRI, eUQs (3OGQ GdaGQhb ddGSJKeGQGJ GdKbGajIs, 2024)
(3cdfG ffHgQ HGdCWaGd GdPjf jJUQahf HWQjbI egPHI Ef SdSdI (B"(3GdPcGA GdGLJeGYj ddCWaGd (B" (3HeKGHI eMGhdI efG dJTLjY GdCWaGd Ydi GdJUQa HWQjbI UMjMI hegPHI hdjJYdehG GdeRjO Yf HYV GdcdeGJ GdSGMQI GdJj fJWdY LejkYG dSeGYgG aj MjGJfG GdjhejIs
(3GdJQHjI h GdWads
Keywords: (3Yde faS GdWads